Does the interval slide procedure reduce supraspinatus tendon repair tension?: a biomechanical cadaveric study - Porschke, Felix; Nolte, Philip-Christian; Knye, Christian; Weiß, Christel; Studier-Fischer, Stefan; Grützner, Paul Alfred; Gühring, Thorsten; Schnetzke, Marc (Orthopaedic journal of sports medicine, 2022)
Background: - The benefits of the interval slide (IS) procedure in retracted rotator cuff tears remain controversial. - - Purpose: - The purpose was to evaluate the effect of the IS procedure on repair tension (RT). It was hypothesized that the IS procedure (anterior IS [AIS], posterior IS [PIS], and intra-articular capsular release [CR]) would reduce the RT of a supraspinatus tendon. - - Study Design: - Controlled laboratory study. - - Methods: - A total of 31 Thiel-embalmed human cadaveric shoulders (mean age, 74 years; range, 68-84 years) were tested. Full-thickness supraspinatus tendon tears were created, and 1 cm of tendon was resected to simulate a retracted defect. Shoulders were randomized into intervention (n = 16) and control (n = 15) groups. In all shoulders, the load during tendon reduction to footprint was measured, an endpoint was defined as maximum tendon lateralization before 50 N was reached, and the RT (load during lateralization to endpoint) of the native tendon (t1) was evaluated. In the intervention group, AIS (t2), PIS (t3), and CR (t4) were performed in order, with RT measurement after each step. In the control group, RT was assessed at the same time points without the intervention. - - Results: - A complete reduction of the tendon was not achieved in any of the shoulders. Mean maximum lateralization was 6.7 ± 1.30 mm, with no significant differences between groups. In the intervention group, the overall IS procedure reduced RT about 47.0% (t1 vs t4: 38.7 ± 3.9 vs 20.5 ± 12.3 N; P < .001). AIS reduced RT significantly (t1 vs t2: 38.7 ± 3.9 vs 27.4 ± 10.5 N; P < .001), whereas subsequent PIS (t2 vs t3: 27.4 ± 10.5 vs 23.2 ± 12.4 N; P = .27) and CR (t3 vs t4: 23.2 ± 12.4 vs 20.5 ± 12.3 N; P = .655) did not additionally reduce tension. Comparison between groups at t4 revealed a reduction of RT of about 47.8% (control vs intervention: 39.3 ± 4.0 vs 20.5 ± 12.3 N; P < .001). - - Conclusion: - The IS procedure reduces RT of the supraspinatus tendon in human cadaveric shoulders. However, performing PIS and CR subsequent to AIS does not reduce tension additionally. - - Clinical Relevance: - These findings provide surgeons with a biomechanical rationale regarding the efficacy of the IS procedure.
Gesehen am 02.06.2022